Clinical characteristics of patients diagnosed with COVID-19 in Beijing - Aihua Jin; Benyong Yan; Wei Hua; Dandan Feng; Bin Xu; Lianchun Liang; Caiping Guo (Elsevier, 2020)
This study aimed to determine the clinical characteristics of patients diagnosed with the coronavirus disease 2019 (COVID-19). Clinical data of COVID-19 patients diagnosed between January 28, 2020 and February 23, 2020 at the Beijing You'an Hospital were summarized and analyzed. Overall, 45 (18 men and 27 women) patients were included in this study. The average age of patients was 58 years (range, 7-94 years). Furthermore, 21 patients (47%) experienced underlying chronic diseases, with another four patients (9%) having three or more chronic diseases simultaneously. The first symptoms appeared at the onset of illness onset include fever in 36 patients (80%), cough in 23 patients (51%), and expectoration in 15 patients (33%), respectively. Patients may experience hepatic and renal injury as well as abnormal myocardial enzymes in varying degrees. Senior patients (≥58) and accompanying chronic diseases were considered as independent predictors for developing a severe and critically ill population with increased mortality. Laboratory results regarding the NEU percentage, NLR, ALC, and C-reactive protein levels were considered significant in predicting clinically critical disease or for prognosis assessment and thus require further studies. COVID-19 may affect multiple organs of the human body. Glucocorticoid is considered effective in the treatment of patients diagnosed with severe COVID-19.